Oxidation behaviors of ZrB2 based ultra-high temperature ceramics under compressive stress - Jin, X.; Li, P.; Hou, C.; Wang, X.; Fan, X.; Lu, Chunsheng; Xiao, G.; Shu, X. (Elsevier Science Ltd, 2019)
ZrB2 based ultra-high temperature ceramic (UHTC) is one of the most promising materials for thermal protection systems. This paper focuses on the oxidation behaviors of ZrB2 under compressive stress. ZrB2 UHTC is fabricated with nano-sized powders at 1500 °C, which is a relative low temperature. Nanoindentation tests are conducted to measure the basic mechanical properties of sintered samples. Results of nanoindentation show that ZrB2 is prepared with good mechanical properties. Oxidation tests are performed under different stress states and temperatures, and oxidation mechanisms and microstructure evolution are discussed. As the oxidation proceeds, ZrO2 grains grow slowly at 1000 °C, but fast at 1200 °C. When oxidized over 1400 °C, ZrO2 grains fuse and micro-sized pores form on the surface due to the release of gaseous oxidation products. The thickness of oxide layer on the samples almost keeps unchanged under various compressive loads. Compared with the stress state, microstructure has a more obvious effect on the oxidation rate. The results in this paper provide a better understanding on the oxidation mechanism of ZrB2 based UHTCs.